Treatment of waldenstrom macroglobulinemia with 2-chlorodeoxyadenosine - Dimopoulos, M.A.; Kantarjian, H.; Estey, E.; O'Brien, S.; Delasalle, K.; Keating, M.J.; Freireich, E.J.; Alexanian, R. (Annals of Internal Medicine, 1993)
Objective: To evaluate the activity of 2-chlorodeoxyadenosine (2CdA) in the treatment of patients with Waldenstrom macroglobulinemia. ■ Design: Uncontrolled phase II trial. ■ Setting: Tertiary, referral cancer center. ■ Patients: Twenty-nine consecutive, symptomatic patients with Waldenstrom macroglobulinemia, of whom 9 were previously untreated. ■ Intervention: 2-Chlorodeoxyadenosine was administered as a continuous intravenous infusion at a dose of 0.1 mg/kg body weight per day for 7 days. Only two courses of 2CdA were given and responding patients were then followed without further treatment. ■ Measurements and Main Results: A total of 17 (59%) patients responded, including all of those who were newly diagnosed and 40% of those who had failed previous therapies. Treatment was well tolerated except for one death in a patient who had presented with severe pancytopenia. With a median follow-up of 7 months, only one responding patient has relapsed. ■ Conclusion: 2-Chlorodeoxyadenosine is a nucleoside analog that was effective in most patients with Waldenstrom macroglobulinemia and was associated with little toxicity.